Medication Safety Improves after Implementation of Positive Patient Identification - Higgins, T.; Heelon, M.; Siano, B.; Douglass, L.; Liebro, P.; Spath, B.; Kudler, N.; Kerr, G. (Applied Clinical Informatics, 2010)
Objective: To report the incidence and severity of medication safety events before and after initiation of barcode scanning for positive patient identification (PPID) in a large teaching hospital.Methods: Retrospective analysis of data from an existing safety reporting system with anonymous and non-punitive self-reporting. Medication safety events were categorized as “near-miss” (unsafe conditions or caught before reaching the patient) or reaching the patient, with requisite additional monitoring or treatment. Baseline and post-PPID implementation data on events per 1,000,000 drug administrations were compared by chi-square with p<0.05 considered significant.Results: An average of 510,541 doses were dispensed each month in 2008. Total self-reported medication errors initially increased from 20 per million doses dispensed pre-barcoding (first quarter 2008) to 38 per million doses dispensed immediately post-intervention (last quarter 2008), but errors reaching the patient decreased from 3.26 per million to 0.8 per million despite the increase in “near-misses”. A number of process issues were identified and improved, including additional training and equipment, instituting ParX scanning when filling Pyxis machines, and lobbying for a manufacturing change in how bar codes were printed on bags of intravenous solutions to reduce scanning failures.Conclusion: Introduction of barcoding of medications and patient wristbands reduced serious medication dispensing errors reaching the patient, but temporarily increased the number of “near-miss” situations reported. Overall patient safety improved with the barcoding and positive patient identification initiative. These results have been sustained during the 18 months following full implementation.
Keywords: Patient safety; pharmacy; positive patient identification; harm scores; computerized provider order entry; informatics